(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2020)
The essay proposes to connect different elements (narrative, thematic, but also related to gameplay and level design) of the video game The Legend of Zelda: The Wind Waker (Nintendo 2002), to a broader dimension, comparable to the maritime epic. The research is introduced by a defining question on the approach of the concept of epic to video games. Then, the contribution focuses on the case study, juxtaposed by other video games in which can be traced an adventurous exploration of the sea. The comparison is focused, in particular, between the Wind Waker and the Odyssey, to which this video game has already been compared on several occasions, without however going into depth on their points of contact. Within the popular saga The Legend of Zelda, the case of Wind Waker is the only one in which the hero’s journey is closely intertwined with the maritime elements, through encounters with sea monsters, shipwrecks and mysterious underwater worlds.